EXOGENOUS ABSCISIC ACID INCREASES RESISTANCES AGAINST ABIOTIC STRESS AND IMPROVE FRUIT QUALITY OF GRAPE - Jin Wang; Hui Xia; Li-Jin Lin Hao He Dong Liang; Xiu-Lan Lv (Journal of Animal and Plant Sciences, 2016)
The objective of this study was to determine the stress resistance responseand fruit quality of grapesto exogenous abscisic acid (ABA). Five concentrations (100, 150, 200, 250 and 300 mg/L) of ABA were tested to evaluate its protective activityin grape leaves and fruit quality of 3-year-old ‘Red Globe’ grape, cultivated under the plastic rain shelter. It was found that additionof ABA significantly decreased the level of electrolyteleakage and lipid peroxidation, enhanced the activitiesof superoxide dismutase, peroxidase, proline content and soluble sugars. Meanwhile, exogenous ABA improved the anthocyanin, soluble solids, titrable acidity and AsA. Nevertheless, it had less effect on fruit shape index and weight of grape fruit (bunch and single berry). It was concluded that exogenous ABA may increase stress resistances and improve fruit quality of grape.
Keywords: ABA; Grape; Stress resistance; Fruit quality